Penyesuaian Pernikahan pada Pasangan Perjodohan - Angraeni, Dwi Muslimah; Mustary, Emilia (Institut Agama Islam Negeri Parepare, 2023)
ABSTRACT The research uses qualitative phenomenological research methods and data collection techniques, namely in-depth interviews. The data analysis technique used is qualitative data analysis which consists of: (a) data reduction (b) data presentation, and (c) drawing conclusions. The data source was obtained from 5 married couples who were arranged marriages and were ready to provide some information to researchers. The results of this research can be stated that the form of adjustment to marriage in arranged marriage couples in Sabbang Paru Village, Lembang District, Pinrang Regency is through 4 aspects, namely adjustment to the partner in the form of always building communication, understanding the partner's condition, being open to each other, and understanding each other. Sexual adjustment consists of always building communication before sexual intercourse, conveying complaints and desires during sexual intercourse. Financial adjustments in the form of couples always communicating about the family's income and expenses so that there are no misunderstandings. Adjustments with your partner's family consist of always building communication with your partner's family and always visiting your partner's family home. Efforts to control conflict in arranged marriage couples include using coping strategies, planful problem solving, which means analyzing every situation that causes problems and trying to find direct solutions to the problems faced and turning to religion, which means returning to religious teachings, namely efforts to implement and improve religious teachings. which is adhered to.